Decelerated carbon cycling by ectomycorrhizal fungi is controlled by substrate quality and community composition. Issue 2 (8th November 2019) - Fernandez, Christopher W.; See, Craig R.; Kennedy, Peter G.
Summary: Interactions between symbiotic ectomycorrhizal (EM) and free‐living saprotrophs can result in significant deceleration of leaf litter decomposition. While this phenomenon is widely cited, its generality remains unclear, as both the direction and magnitude of EM fungal effects on leaf litter decomposition have been shown to vary among studies. Here we explicitly examine how contrasting leaf litter types and EM fungal communities may lead to differential effects on carbon (C) and nitrogen (N) cycling. Specifically, we measured the response of soil nutrient cycling, litter decay rates, litter chemistry and fungal community structure to the reduction of EM fungi (via trenching) with a reciprocal litter transplant experiment in adjacent Pinus ‐ or Quercus ‐dominated sites. We found clear evidence of EM fungal suppression of C and N cycling in the Pinus ‐dominated site, but no suppression in the Quercus ‐dominated site. Additionally, in the Pinus ‐dominated site, only the Pinus litter decay rates were decelerated by EM fungi and were associated with decoupling of litter C and N cycling. Our results support the hypothesis that EM fungi can decelerate C cycling via N competition, but strongly suggest that the 'Gadgil effect' is dependent on both substrate quality and EM fungal community composition. We argue that understanding tree host traits as well as EM fungal functional diversity is critical to a more mechanistic understanding of how EM fungi mediate forest soil biogeochemical cycling. Abstract : See also the Commentary on this article by Smith & Peay, 226 : 292–294 .